Costs of retail payments: An overview of recent national studies in Europe - Kerstin Junius; Lucas Devigne; Juha Honkkila; Nicole Jonker; László Kajdi; Johana Kimmerl; Lukas Korella; Rodrigo Matos; Nadine Menzl; Karolina Przenajkowska; Jelmer Reijerink; Giorgia Rocco; et al. (European Central Bank (ECB), 2022)
The paper provides an overview of studies on the social and private costs of retail payments conducted since 2013 in nine EU countries and collates the results obtained. Social costs of retail payments are the overall costs resulting from providing payment services to society and deriving from the resource costs incurred by all parties along the payment chain. Private costs, in contrast, are the costs incurred by the individual stakeholder only, such as banks and other payment intermediaries. Understanding the social and private costs of retail payments is crucial for assessing the impact of the rapidly changing retail payment landscape, such as the shift to electronic payments, and for designing strategies for moving towards cost efficient retail payments. Despite varying scopes and methodological differences, the analysis reached the following findings: a comparison of results between 2009 and 2016 in Denmark and Italy, between 2015 and 2018 in Poland and between 2009 and 2017 in Portugal, points to decreasing overall social costs for retail payments relative to gross domestic product (GDP). Moreover, the data suggest that changing payment habits - the shift to electronic payments and in particular debit cards - have an impact on unit costs, which represent the costs per transaction. The unit costs of debit card payments have decreased over time and the gap between the unit costs of cash and those for debit cards has narrowed. This suggests that the increasing number of debit card payments, to which high fixed costs are attached, has led to lower unit costs relative to those of cash. The only study on the costs of retail payments in Europe, published as an ECB occasional paper, dates from 2012 and is based on data from 2009.1 Although more recent surveys at national level are available, no single source exists that sheds light on recent information on the costs of retail payments in Europe. Since the national surveys follow different approaches, in terms of both scope and methodology used, for obtaining the costs of retail payments, the results are not easily comparable with each other across countries.
Keywords: D23; D24; O52; E42; 330; social costs; private costs; retail payments; payment instruments